Effect of Ag-doped TiO2 thin film passive layers on the performance of photo-anodes for dye-sensitized solar cells. (1st March 2016) - Usha, K.; Kumbhakar, P.; Mondal, B.
Abstract: Ag-doped nanocrystalline structures of TiO2 in the form of colloidal particles are synthesized by using AgNO3 solution with Acetyl acetone and diacetyl monoxime modified titanium isopropoxide precursor. Thin layers of undoped and Ag-doped TiO2 sols are deposited on conducting glass substrate by dip coating technique. The thin films are developed by repeated coating of the sols for 5, 10 and 15 times which results the formation of thin layers with different thickness. These layers are annealed at 450 °C so as to use them as bottom/ seed layers of fabricating photoanodes for dye sensitized solar cells. The optical properties of undoped and Ag-doped TiO2 thin layers are studied in details. Effective mass model is used to find the particle size and peak wavelength relationship for the nanocrystals of TiO2 . Quantum efficiency of dye sensitized solar cells assembled using the fabricated photoanodes with Ag-doped TiO2 shows increase in efficiency by about 4% in comparison to the undoped TiO2 layers. The improved performance is attributed to ease of transportation of electron through passivating layer to the external circuit.